MODEL OF ENGLISH LEARNING BASED ON COLLABORATIVE THEORY TO IMPROVE INDONESIAN’ SPOKEN COMMUNICATION ABILITY - Asmawati, Nur (ETERNAL (English, Teaching, Learning, and Research Journal), 2018)
This study aims at findings whether collaborative method can improve students' spoken communition or not. This study use quasi experimental design with Posttest-Only, Non-Equivalent Control Group Design. The sample of this research were student’s of State Institute for Islamic Studies (IAIN) Palu. The instrument in this research was speaking English test ability. The tests were carried out in five times with different learning themes. Data analysis was performed by descriptive statistics and inference and presented in the form of percentages, frequency, min and statistical analysis in t test comparison (t-test) and Pearson correlation test. The researcher finds distribution of scores for the students’ spoken communication ability posttest is normal and variance-covariance for the dependent variables is homogeneous across the independent variables. The researcher finds a significant difference between the experimental class taught by a learning model of three theories collaboration and controclass taught by conventional learning model. The result of students] spoken communication ability on first test had higher compared second test. Similarly, also with the students’spoken communication abilities between the second tests with the third test, the third test with the fourth test, and the fourth test with the fifth test was very significant. The researcher also finds increased English spoken communication ability in experimental class. Improvement of spoken communication is due to model of learning English based on collaborative theory